At the Roots of the New Right‐Wing Extremism in Portugal: The National Action Movement (1985–1991) - Marchi, Riccardo (Totalitarian movements and political religions, 2010)
Since the mid‐1980s, the Portuguese Radical Right has deeply changed its political beliefs. The traditional radical right that emerged from the authoritarian regime and was characterised by the ‘multiracial and pluri‐continental imperial myth’ has been replaced by a new radical right showing an ethno‐nationalist political identity. This change was played, for the first time, by the Movimento de Acção Nacional [MAN, National Action Movement]: a radical group founded in 1985. MAN introduced the political speech and militancy typical of the more extreme European groupuscular rights in Portugal, fusing both the ultra‐nationalism of the old radical right and the neo‐Nazi racism of the skinhead subculture. The attention given to MAN’s growing activism by Portuguese media and judicial authorities made it the most important radical right movement in contemporary Portugal after the transition to democracy.